2020
DOI: 10.1017/jfm.2020.558
|View full text |Cite
|
Sign up to set email alerts
|

Separation scaling for viscous vortex reconnection

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
2
7
2
Order By: Relevance
“…2014; Villois, Proment & Krstulovic 2017). Our recent results on thin core vortices show that such 1/2-power scaling is also valid for classical viscous reconnection (Yao & Hussain 2020 a , c ).…”
Section: Flow Physics For Zero Initial Twist Casessupporting
confidence: 52%
“…2014; Villois, Proment & Krstulovic 2017). Our recent results on thin core vortices show that such 1/2-power scaling is also valid for classical viscous reconnection (Yao & Hussain 2020 a , c ).…”
Section: Flow Physics For Zero Initial Twist Casessupporting
confidence: 52%
“…2, using different symbols, the pre-factor measurements obtained in previous works [15,16], which corroborate even further our results. Finally note that in a recent work [19], it has been reported that vortex reconnections in Navier-Stokes also display a clear t 1/2 scaling, a coefficient A − ∼ 0.3 − 0.4 and the same time asymmetry A + > A − . Note that the Biot-Savart analytical calculations of reference [20] and the LIA based ones of [21], predict A − ∼ 0.47 and A − = 0.427 respectively, which are in agreement with our GP measurements.…”
mentioning
confidence: 68%
“…Recently, Yao & Hussain (2020 a ) observed that the scaling of approaches when the core size of the tube becomes small. This scaling can be obtained through dimensional analysis based on the assumption that reconnection is a local event and the circulation is the only relevant quantity, and has been observed numerically as well as experimentally, both in quantum and classical fluids (Villois, Proment & Krstulovic 2017; Kimura & Moffatt 2018; Fonda, Sreenivasan & Lathrop 2019; Yao & Hussain 2020 c ). It would be interesting to investigate whether such scaling can be affected by the presence of axial flows.…”
Section: Results For the Counter-polarized Casesmentioning
confidence: 99%
“…The rate of decrease increases with (inset in figure 6 b ). Recently, Yao, Yang & Hussain (2021) showed that for a rectilinear Batchelor vortex column, the relative decay rate of enstrophy varies from to when increases from to (here, is the vortex core size). The rapid decay of enstrophy for strongly polarized cases is consistent with the claim that helicity may inhibit energy transfer due to the role of helicity in depleting nonlinear interaction (Wu et al.…”
Section: Results For the Counter-polarized Casesmentioning
confidence: 99%